Advances in risk management - Gregoriou, Greg N. 1956- (Palgrave Macmillan, 2007)
This important book brings together an edited series of papers about risk management and the latest developments in the field. Covering topics such as Stochastic Volatility, Risk Dynamics and Portfolio Diversification, this book is vital for optimal portfolio allocation for private and institutional investors, and is an indispensable tool
Keywords: Finance; Business enterprises / Finance; Management; International business enterprises; Corporations / Finance; Investment banking; Securities; Risk management; Anlagepolitik; Portfolio Selection; Risikomanagement; Aufsatzsammlung